Mass Tourism as A Benefactor and A Curse - Martin SCHMIDT-SCHWEFLINGHAUS (Communications of International Proceedings, 2025)
Tourism as a wide-spread phenomenon did not occur until the 1960s, with an emerging prosperous middle-class in Europe and the United States of America spending a significant portion of their income for tourist activities. This development rapidly gained momentum, leading to the phenomenon of mass tourism and eventually overtourism. It is especially underdeveloped regions and countries that profited immensely from this, because tourism created jobs and lots of opportunities. With mass tourism growing constantly, many cities and regions were taken over by the tourist industry in such a way that environmental problems and societal disruptions have turned the benefits upside down, and many observers are asking the question whether the benefits still outweigh the disadvantages. The issue of mass tourism has meanwhile caused cultural upheavals by locals who are affected by this phenomenon, and the tensions do not seem to be calming down. In metropolitan areas like that of Barcelona, overtourism has led to a shrinking supply in affordable housing, and many inhabitants are wondering whether mass tourism is still a net positive. In Santorini, the summer season puts the locals under a massive pressure, with several cruise ships arriving and leaving on the same day. With no simple solutions at hand, the question will be whether there will be radical shifts and turnarounds or gradual adjustments within the framework dominated by mass tourism.
Keywords: Mass tourism; Overwhelmed tourist strongholds; Overtourism; Cultural upheavals; Local self-determination